Article Commentary: Calling for Help? Considering Function and Meaning when Patients Drunk-Dial Psychotherapists - Kelly Serafini; Donna LaPaglia; Matthew Steinfeld (SAGE Publishing, 2013)
Drunk-dialing is a term documented in both popular culture and academic literatures to describe a behavior in which a person contacts another individual by phone while intoxicated. In our collective clinical experience we have found that clients drunk-dial their clinicians too, particularly while in substance use treatment, and yet there is a noticeable absence of research on the topic to guide clinical decision-making within a process-based understanding of these events. As the parameters within which psychotherapy takes place become increasingly technologized, a literature base to document clients' idiosyncratic use of technology will become increasingly necessary and useful. We provide a brief review of the existing research on drunk-dialing and conclude with specific questions to guide future research and practice.